2004
DOI: 10.1097/01.inf.0000114904.21616.ba
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infections after pediatric cardiovascular surgery

Abstract: Age <1 month and longer duration of surgery were independently associated with hospitalized SSI after CV surgery in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
3
11

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 12 publications
9
76
3
11
Order By: Relevance
“…Similar results have been reported previously in adult patients with cardiothoracic operations [114]. [20] 1580 (1580)…”
Section: Surgical Site Infectionssupporting
confidence: 80%
See 4 more Smart Citations
“…Similar results have been reported previously in adult patients with cardiothoracic operations [114]. [20] 1580 (1580)…”
Section: Surgical Site Infectionssupporting
confidence: 80%
“…Most earlier studies have reported the finding that preoperative hospitalization for more than two days increased the risk for SSI [20,22,23]; only one of them reported no association [21]. The duration of surgery or perfusion time [20][21][22] and having an open chest after the operation [23,24] were identified as risk factors for infection in earlier studies, but we found no such association.…”
Section: Risk Factors For Surgical Site Infectionscontrasting
confidence: 49%
See 3 more Smart Citations